Using Phonetic Transcription App as Media of Teaching Phonetics in English Pronunciation Skill - Tira Nur Fitria (EDUCAFL : Journal of Education of English as Foreign Language, 2023)
This research stimulates the use of toSpeech phonetic transcription app as media for teaching phonetics in English pronunciation. This research is descriptive qualitative. The analysis shows that in using toPhonetic app, we as teachers or lecturers can click the website https://tophonetics.com/.  The apps show 1) several languages available. 2) a column box for pasting English text, 3) an option of English accents both British and American with several choices of a male or female voice. 3) an option to show the phonetic transcription including transcription only, transcription slide by side with English text, and transcription line by line with English. 4) an option to set the pronunciation speed. In using toPhonetic app, we as teachers or lecturers can choose the English language to teach pronunciation. We paste English text into the available column box and choose from a male or female voice and an English accent both British and American. We also can set the pronunciation speed. If we click the sound of pronunciation, the chosen voice and accent will pronounce each word and shows the phonetic transcription in British and American accent. We can play the sound and ask the students to be concerned with the phonetic transcription and imitate the sound with an American accent. Given the limited time available for English class, pronunciation is sometimes the most disregarded part of language learning. However, when the pronunciation of the learner is expected to be good or native-like, as is the case when a language teacher or lecturer is involved, opportunities for students to do self-study inside and outside of class should be considered, of them is utilizing toSpeech as an app for their learning English pronunciation.